Pemberdayaan Posyandu Lansia di Desa Borisallo, Kec. Parangloe, Kab. Gowa - Wardiah Hamzah; Nurfachanti Fattah (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
Integrated Service Post for the Elderly or Posyandu Lansia is a form of health service organized by the community with support from the government, which aims to improve the quality of life of the elderly. Posyandu cadres become partners in this service facing the following problems; (1) Posyandu cadres have not been trained in managing Posyandu Lansia activities (2) Incomplete supporting equipment such as tensiometers, scales and other simple health check-up tools at Posyandu Lansia. The solutions are: (1) Training of Posyandu cadres in managing the administration and program activities of Posyandu Lansia, (2) Provision of supporting tools for Posyandu Lansia activities in Borisallo Village, Parangloe District, Gowa Regency. The activity will be carried out for 4 months with funding sources from the UMI Waqf Foundation. Results of the implementation of PKM activities (1) Training of Posyandu Lansia cadres for 6 Posyandu Lansia cadres in Borisallo Village, Parangloe District, Gowa Regency. (2) Provision and explanation of the use of supporting tools for Elderly Posyandu activities such as scales, microtoists and thermometers. It is recommended that (1) Elderly Posyandu cadres motivate the Elderly to diligently come to the Posyandu every month so that they can have regular health checks (2) to anticipate Elderly who are lazy to go to the Elderly Posyandu.